A meta-analysis of studies of nurses' job satisfaction - Zangaro, George A.; Soeken, Karen L. (Research in nursing & health, 2007)
Although several variables have been correlated with nursing job satisfaction, the findings are not uniform across studies. Three commonly noted variables from the nursing literature are: autonomy, job stress, and nurse–physician collaboration. This meta‐analysis examined the strength of the relationships between job satisfaction and autonomy, job stress, and nurse–physician collaboration among registered nurses working in staff positions. A meta‐analysis of 31 studies representing a total of 14,567 subjects was performed. Job satisfaction was most strongly correlated with job stress (ES = −.43), followed by nurse–physician collaboration (ES = .37), and autonomy (ES = .30). These findings have implications for the importance of improving the work environment to increase nurses' job satisfaction. © 2007 Wiley Periodicals, Inc. Res Nurs Health 30:445–458, 2007.